The Sounds of West Africa. - Dor, George Worlasi Kwasi (African Studies Review, 2003)
A review of Gloria J. Gibson and Daniel B. Reed's CD-ROM set, Music and Culture of West Africa: The Straus Expedition, is presented. It is explained that the CD-ROM set is based on Laura Boulton's 1934 recording trip to colonial West Africa, and that it documents the music and culture of 21 ethnic groups, as well as providing information on the aims and objectives of the expedition, its funding, field equipment, route, field experiences, and its relevance to the field of ethnomusicology.